1995
DOI: 10.1111/j.2044-8325.1995.tb00593.x
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive—innovative (A—I) cognitive styles of male and female project managers: Some implications for the management of change

Abstract: This paper reports for the first time the results of a study of the adaptive–innovative cognitive style of the managers of change projects. The Kirton Adaption–Innovation Inventory (KAI) was completed by 133 such managers and the mean KAI score of 109.4 (SD = 14.0) indicates a preferred innovative approach to making decisions and solving problems when managing projects involving significant change. This result is consistent with those of other studies which have shown that activities which involve working acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…marketing, sales or personnel) the mean is skewed towards innovation (Kirton, 1989: 64). Tullett (1995), in a study of 133 project managers, found they had a preferred innovative approach to decision making, problem solving and project management involving signi cant change. Their result suggests that activities which involve working across functional boundaries are generally undertaken by individuals with an innovative style.…”
Section: Vocational and Occupational Preferencesmentioning
confidence: 97%
“…marketing, sales or personnel) the mean is skewed towards innovation (Kirton, 1989: 64). Tullett (1995), in a study of 133 project managers, found they had a preferred innovative approach to decision making, problem solving and project management involving signi cant change. Their result suggests that activities which involve working across functional boundaries are generally undertaken by individuals with an innovative style.…”
Section: Vocational and Occupational Preferencesmentioning
confidence: 97%
“…While the occurrence of female managers holding positions within the TMT is a relatively recent phenomenon (Krishnan and Park, 2005), there has been a growing interest in uncovering the influence of women in the strategic decision-making process in the last years. Gender diversity provides a more innovative (Tullett, 1995), proactive (Bass and Avolio, 1994), and cautious way of thinking (Huang and Kisgen, 2013) that increases the quality of the decision-making and augment the scanning of the environment (Parola, Ellis and Golden, 2015), which in turn may result into a higher internationalization level.…”
Section: Tmt Functional and Demographic Diversitymentioning
confidence: 99%
“…In the example given in the findings, the candidate was a high``E'' scoring innovator who worked very closely and successfully with a low``E'' scoring adapter. A number of studies reported that, although cognitive style remains constant over time, collaborative efforts can produce changes in behaviour and develop appropriate coping strategies (Tullett, 1995). In relation to this example, it was suggested that this would be more likely with innovators (Tullett, 1995).…”
Section: Application Of the Research Findingsmentioning
confidence: 99%